Comparison of the clinical efficiacy of azithromycin and cerufoxime axetile in the treatment of patients with acute otitis media - Celik, O.; Gok, U.; Yalcin, S.; Karlidag, T.; Susaman, N.; Cetinkaya, T. (My University, 1997)
This study was prospectively planned to compare the efficiacy of azithromycin which is a new antibacterial agent and cefuroxine axetile which is commonly used second-generation cephalosporin for the treatment of acute otitis media. Patients diagnosed with acute otitis media received three days of azithromycin (10 mg/kg/day in children, 500 mg/day in adults in single daily dose) or ten days of cefuroxime axetile (40 mg/kg/day in children, 500 mg/day in two divided doses). Clinical efficiacy was evaluated at the beginning and on days 4-6, 10-14 and 30 of the treatment. Microbiologic assessments were performed in patients provided informed consent. Fifty-six patients were enrolled in the study. Thirty-one patients received azithromycin and twenty-five cefuroxime axetile. There were no significant differences in symptoms and signs between the patient groups with acute otitis media (p>0.05). Microbiologic assessments were performed in thirty- seven ear samples and the primary pathogen was found to be Streptococcus pneumoniae. Four patients in azithromycin-treated group and three patients in cefuroxime axetile-treated group were excluded for lack of efficiacy. Moreover, nine patients in each group were excluded for inadequate follow- up; thus, the study which was started with fifty-six patients could be finished with thirty patients. Satisfactory clinical outcome observed in 82% of azithromycin-treated group and in 81% of cefuroxime axetile-treated group. The gastrointestinal complaints were the most common side effects. No patient discontinued treatment because of adverse events. Statistically significant difference between clinical responses in azithromycin-treated and in cefuroxime axetile-treated groups was not found. Compliance was better in azithromycin-treated patients than in cefuroxime axetile-treated patients.
Akut otitis media tedavisinde azitromisin ve sefuroksim aksetil'in etkinklirinin karsilastirilmasi
Keywords: Acute otitis media; Azithromycin; Cefuroxime axetile